2012
DOI: 10.3113/fai.2012.1139
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Forefoot Surgery: A Cadaveric Study

Abstract: Background: Minimally invasive surgery (MIS) aims to improve cosmesis and minimize soft tissue disruption by using small skin incisions. When using MIS in the forefoot, there is concern about iatrogenic neurovascular and tendon damage. The aim of this anatomical study was to assess the risk of iatrogenic injury while performing MIS techniques. Methods: Ten normal cadaveric feet were used. All of the procedures were performed in a cadaveric lab using a mini-C-arm by two surgeons: a consultant who has attended a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 9 publications
3
44
1
3
Order By: Relevance
“…The procedure was conducted on fourteen fresh frozen cadaveric below knee specimens. This is comparable to the previous literature using a cadaveric model in which 10 to 30 specimens were used [7,12,17,18]. Of the fourteen specimens four clinically exhibited hallux valgus deformity.…”
Section: Methodssupporting
confidence: 85%
“…The procedure was conducted on fourteen fresh frozen cadaveric below knee specimens. This is comparable to the previous literature using a cadaveric model in which 10 to 30 specimens were used [7,12,17,18]. Of the fourteen specimens four clinically exhibited hallux valgus deformity.…”
Section: Methodssupporting
confidence: 85%
“…One of the feared risks of MIS is iatrogenic 17 damage to neurovascular and tendinous structures. One cadaveric 18 study has deemed MIS forefoot surgery safe and has reported minimal risk, which is consistent with clinical studies in the literature, although no anatomical references were provided [5]. Q4 MIS for hallux valgus was described amongst the first techniques in the development of this discipline.…”
mentioning
confidence: 58%
“…Clinical series and comparative studies have been published [47][48][49][50]. Additionally, cadaveric results [51,52], technique reports [53], and radiological validations [54,55] have been described. Despite the fact that for some authors percutaneous surgery of the forefoot lacks scientific support [56][57][58], recently two systematic reviews published support its indication in hallux valgus surgery [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Current Situation and Indicationsmentioning
confidence: 99%